2019
DOI: 10.5114/fmpcr.2019.82972
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and burden of informal caregivers providing care for patients with low function agility in the home environment

Abstract: Background. Providing care to patients with low function agility in the home environment becomes a burden and leads to the worsening of the informal caregiver's quality of life. Objectives. aim of the research was to assess the quality of life of informal caregivers in the context of their burden linked to the care provided to chronically ill patients with low function agility in the home environment. Material and methods. research was conducted in five public healthcare facilities, from september 2016 until F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The results of the present study also demonstrated that increasing caring burden predicted a decrease in QoL, and an increase in caring burden would lead to a decrease in a caregiver's QoL, which is consistent with studies by Adili et al [49], Farzi et al [50], Bartoszek et al [51] and Young et al [52].…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study also demonstrated that increasing caring burden predicted a decrease in QoL, and an increase in caring burden would lead to a decrease in a caregiver's QoL, which is consistent with studies by Adili et al [49], Farzi et al [50], Bartoszek et al [51] and Young et al [52].…”
Section: Discussionsupporting
confidence: 93%
“…Bartoszek et al Also researched the quality of elderly people's life quality (those who were caring for chronically sick people at home). In their research, 138 people took part at the age of 59-84, in which case the average age was 68.57±11.6 according to WHOQOL-AGE the average of their life quality was 70.14±15.31 in subscale 1 -71.11±13.88, and subscale 2 -69.15±18.55 [21]. From the research done by Raggi et al On a representative group of 5639 people, out of whom 2863 people are from Poland (age 44.6±18.3) the level of life quality was 69.9±14.6 and it was lower than the life quality of people from Spain (n=2256) or Finland (n=520), although the average age of surveyed people in the case of both countries was higher [22].…”
Section: Discussionmentioning
confidence: 99%